Kelly Covert, KCPR radio talk host - John Duong::::::photographer::: (1994)
Kelly Covert, host of KCPR radio talk show "My people, your people," a show that centered around people with disabilities. Covert was blind. This photo was published in an October 20, 1994 issue of the Mustang Daily in an article titled "A different kind of vision."